(untitled) (Zoo Botanica, 2025)
Watermelon can be considered a potential food snack by the health-conscious consumers. Due to its phytochemicals such as vitamin C and lycopene, and total phenolic content containing anti-cancer and antioxidant properties. It helps with healthy diets which leads to a significant decrease in chronic diseases, hypertension and cardiovascular diseases. Watermelon is one of the major vegetables cultivated in Sahiwal district. This study was aimed to assess the genetic variability of lines of this Institute. In 2017, Sixteen genotypes were collected from various regions of Faisalabad (Lodhra, Sahiwal, Jaranwala, Tandliawala, and Samundari), China and Turkey to evaluate them for quantitative and qualitative traits. These genotypes were selfed over six to seven consecutive years to ensure homozygosity. These inbred lines were further evaluated for quality and yield related traits. The accessions SBA (red flesh) (TSS: 12), 1HB (yellow flesh) (TSS: 11), Shannua (orange flesh) (TSS: 14), 6. No (red flesh) (TSS:13), 802 (yellow rind & red flesh) (TSS: 11) were identified promising for future breeding program based on Total Soluble Solids (TSS) and fruit shape. High genetic variability has been observed among lines for the quality traits including fruit shape, size and color. Statistical procedure including ANOVA, PCA and correlation have been used to study variability for different trait among inbred lines. Significant positive correlation has been present among quantitative traits i.e, leaf width, internode length, number of primary branches, vine length, fruit weight, days of harvesting and yield per plant. Principal component analysis identified two main clusters, suggesting a clear distinction based on morphological characters. Eigan values greater than zero indicate that the corresponding principal component contributed highly to variance of different characters. Correlation studies suggested that fruit weight is strongly correlated with yield per plant.